Diálogo como experiência formativa : efetividade pedagógica de uma práxis hermenêutica na educação - Braun, Claudio Damião (2022)
This thesis aims to reflect on the pedagogical effectiveness of hermeneutic praxis in education, taking Hans-Georg Gadamer's Philosophical Hermeneutics as a reference. The aim is to tackle the problem of weakening dialogic action in current education. Indeed, the weakening of the capacity for dialogue seems to be leading contemporary society to a kind of monologue or a disguised dialogue that does not meet the requirements of true dialogue. Such weakening contributes to the deconstruction of social values and to the predominance of exploitation of the other in the name of freedom and individual rights. Starting from a diagnosis that led us to verify a weakening of dialogic action in current education, strongly influenced by a tendency that privileges technical-instrumental action to the detriment of dialogic rationality, we analyze how this practice interferes in the formation of human relationships, in order to generate an increase in the incapacity for the development of “living dialogue” and understanding between individuals. In confrontation with this instrumentalizing tendency of rationality, we oppose and defend the pedagogical effectiveness of a hermeneutic praxis that takes dialogue as a guiding principle as a formative experience. In order to do so, we make use of Hans-Georg Gadamer's philosophical hermeneutics, seeking, in the principles that he develops, a perspective that enables dialogic practice in education. As a way of critical confrontation, we seek to guide dialogue as essential in the training experience, demonstrating the importance of the hermeneutic principle of dialogical reason and live dialogue in the training process. The conclusion of the thesis points out that an integral formation of the human being requires, in addition to the development of technical formation, formation for dialogue and constant hermeneutic exercise as an essential factor in social relations and in education.